The Historical Development of the Place Name in Armenian (Etymology of ‘Harzhis’ Sacred Area) - Mher Kumunts; Margaryan, Inga; Hasmik Khachatryan; Gayane Mkhitaryan; Gayane Gevorgyan; Nersisyan, Lusine; Viktor Katvalyan (Forum for Linguistic Studies, 2024)
Armenian linguistics still has a lot to do in the field of onomastics. Many place names, tribal names, myth names, and names of objects with material cultural value have not yet received onomastic, historical-comparative, dialectological studies. However, they have historical value and contain important information. Place names are important in the study of Armenian Special Names, which contain a lot of linguistic, historical, ethnographic, and archaeological information about the region. Many place names in Armenian, which exist from prehistoric times, have not yet been studied. Harzhis settlement of Syunik region of the Republic of Armenia has received world recognition due to its sacred landscape. However, there is no study on the toponym until now. Comparing the results of the studies in the fields of different scientific disciplines, we tried to etymology the place name Harzhis. We reconstructed its initial version in the Indo-European proto-language, then compared the formal and semantic changes in the Urartian period, in ancient Armenian (grabarum), in the Syunik dialect area, with related languages. The prehistoric cave, the statues with religious significance, the traditions, and the findings preserved in the settlement are not yet complete to determine the period of existence of the Harjis settlement. Linguistic research allows us to conclude that the settlement is one of the first cultural centers of the Indo-European people in the South Caucasus and the Armenian Plateau.